Transparency or Apparent Transparency in Dutch Municipalities - Anderson, Rick (Public Governance, Administration and Finances Law Review, 2025)
This study focuses on the extent to which Dutch municipalities’ decisions to make personal policy views public actually lead to greater transparency. The research finds that council members perceive increased transparency as a consequence of such decisions. However, the study also observes that administrative resistance may arise against the decision to disclose personal policy views. This resistance has various causes and can take different forms. Some forms of resistance are recognised by council members, while others are not. In the latter case, a degree of apparent transparency may emerge. The use of these unnoticed forms of resistance is strongly associated with the type of disclosure decision that is made. For example, in all cases where the decision was taken to actively disclose all communication, certain information is emphasised, and oral consultation is intensified.